Behavior of Consumers in The Purchase Meat Chicken in Traditional Markets Donggala in Regency (Case Study of Ganti Market) - Arafah, Arafah; Mujayin, Yudi (AgriSains, 2020)
This study aims to determine consumer behavior towards attributes of chicken meat such as meat color, texture, aroma and weight in purchasing decisions, and to analyze the factors that influence behavior. The research was conducted at the Traditional Ganti MarketÂ  of Donggala Regency from August to September 2019. The research used survey methods and interviews with a sample of 40 respondents. Data were analyzed using Multi-attribute Analysis and Multiple Linear Regression. The results showed that the attributes of chicken meat weight were highly considered in making purchasing decisions, followed by the aroma, color and texture of the meat. The results of the Multiple Linear Regression analysis show that the price of chicken meat, income, number of family members, age, gender, education and work together have a positive effect on consumer behavior. However, individually, the ones that have a positive effect on consumer behavior are education and consumer occupation.